Arthroplasty Registries: Improving Clinical and Economic Outcomes - Courtney, P. Maxwell; Markel, David C. (The Journal of Knee Surgery, 2017)
With renewed focus on achieving value for patients in total hip and knee arthroplasty, payors, hospitals, and physicians strive to provide quality care while minimizing cost. Large registry datasets have gained popularity in the United States to track implant survivorship and outcomes after joint replacement. Partnerships among surgeons, insurers, and health systems have improved on earlier administrative datasets from Medicare to measure quality and outcomes. Participation in state and national registries can help surgeons and hospitals gain a financial advantage in several insurers' quality programs and alternative payment models. Although large dataset analysis has its limitations, all health care stakeholders will become increasingly dependent on arthroplasty registries to improve quality and control costs.
Keywords: total knee arthroplasty; total hip arthroplasty; registry; outcomes